Multikulti: uitdaging of ergernis? Een empirische studie naar de opvattingen van scholieren in Duitsland en leerlingen van het confessioneel onderwijs in Nederland - van der Tuin, Leo; Ziebertz, Hans-Georg (Religie & Samenleving, 2007)
A comparison between the Netherlands and Germany, concerning religious, cultural and ethnic plurality seems to be very interesting because Germany has surely never defined itself as a multicultural population, as was historically the case in the Netherlands. While pupils in the highest grades of education are supposed to be the coming leaders in their countries, the question is even more interesting: do they continue the history of their parents? The research questions we formulated focus on their attitude to cultural and religious plurality in general, to their view on the question of truth and salvation in different religions and the relation between religions, and last to their attitude to foreigners, called immigrants in Germany and allochthons in the Netherlands. The outcomes of the research are in some way surprising. Dutch pupils – especially the boys – are more negative about the plurality than their German contemporaries. Belonging to a church in Germany appears to connect with a positive attitude to migrants, while in the Netherlands this isn’t important at all, there is a great indifference on this point: The chain of memory seems to be broken in different ways. For the Netherlands there is much to discuss.